Sequence analysis of the fusion (f) protein cleavage site of four Newcastle disease virus isolates - Ramanujam, Priadarishni; Tan, Wen Siang; Nathan, Sheila; Yusoff, Khatijah (Veterinary Association Malaysia, 2004)
The amino acid sequence of the fusion (F) protein of Newcastle disease virus (NDV) is of particular interest as its virulence is highly dependent on susceptibility to proteolytic cleavage. The F protein precursor, F0' can beproteolytically cleaved to form disulfide-linked F, and F2 chains. The Fa cleavage is a prerequisite for producing infectious particles whereby the nature of the cleavage site correlates with virulence of the virus. Inthis study we determined the F protein gene cleavage site nucleotide sequence ofNDV local isolates 2641191 P2, 5953/89 P3, 1266/89 P3 and 8820/92 P3. Their sequences were also compared with other NDV strains and isolates, such as AF2240, OOIIKS, 011TM, 01lC, 3410/92 P2, 6385/90 P3, V4 Que and F that had previously been determined. The deduced amino acid sequence of this site revealed the pathogenecity of these strains whereby 2641191 P2 and 5953/89 P3 were classified as virulent isolates whilst 1266/89 P3 and 8820/92 P3 were avirulent isolates.